Improving Students’ Writing Skills through Discovery Learning Model - Andung, Loduvikus Irvan Humba Langa; Marsuki, Marsuki; Rosa, Chindy Hanggara (UIBU, 2024)
This research aims to improve students' writing skills through the implementation of the Discovery Learning model. This model is designed to encourage students to be more active in the learning process by discovering concepts and knowledge independently through exploration, observation, and analysis. The research was conducted in 2024 involving students as research subjects. The research approach used was an experimental method with a pre-test and post-test design. Students were given writing tasks before and after the implementation of the Discovery Learning model to measure the improvement in their writing skills. The results showed that the application of the Discovery Learning model significantly improved students' writing skills. Students became more creative, able to develop ideas well, and more confident in compiling their writing. In conclusion, the Discovery Learning model is proven effective in improving students' writing skills. This approach can be applied widely to support English language learning, especially in the development of writing skills.